2015
DOI: 10.1093/mnras/stv1555
|View full text |Cite
|
Sign up to set email alerts
|

A large narrow-band Hα survey at z∼ 0.2: the bright end of the luminosity function, cosmic variance and clustering across cosmic time

Abstract: We carried out the largest (> 3.5 × 10 5 Mpc 3 , 26 deg 2 ) Hα narrow band survey to date at z ∼ 0.2 in the SA22, W2 and XMMLSS extragalactic fields. Our survey covers a large enough volume to overcome cosmic variance and to sample bright and rare Hα emitters up to an observed luminosity of ∼ 10 42.4 erg s −1 , equivalent to ∼ 11M yr −1 . Using our sample of 220 sources brighter than > 10 41.4 erg s −1 (> 1M yr −1 ), we derive Hα luminosity functions, which are well described by a Schechter function with φ * =… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 60 publications
(123 reference statements)
1
58
0
Order By: Relevance
“…We indicate previous UCM works as blue filled circles. The black circles correspond to the studies of Sobral et al (2012) at z ∼ 1.47; Sobral et al (2013) at z ∼ 0.4, 0.84, 1.47, 2.23; Drake et al (2013) at z ∼ 0.25, 0.4, 0.5; Sobral et al (2015) at z ∼ 0.8; and Stroe & Sobral (2015) at z ∼ 0.2. The compilation in Table B.1 of Gunawardhana et al (2013) is included as grey filled circles.…”
Section: Discussionmentioning
confidence: 96%
“…We indicate previous UCM works as blue filled circles. The black circles correspond to the studies of Sobral et al (2012) at z ∼ 1.47; Sobral et al (2013) at z ∼ 0.4, 0.84, 1.47, 2.23; Drake et al (2013) at z ∼ 0.25, 0.4, 0.5; Sobral et al (2015) at z ∼ 0.8; and Stroe & Sobral (2015) at z ∼ 0.2. The compilation in Table B.1 of Gunawardhana et al (2013) is included as grey filled circles.…”
Section: Discussionmentioning
confidence: 96%
“…For a given luminosity, the minimum and maximum redshifts where the emission line can be observed at more than The red curve is a best-fit Schechter function to the red data points, where the solid (dotted) curve is fitted without (with) α fixed. The black curves are the luminosity functions from the literature, where the luminosity range covering the data in each study is shown by thick curve and the other range is shown by thin curve (Ly et al 2007;Drake et al 2013;Stroe & Sobral 2015;Sobral et al 2013). 5σ are calculated based on the filter transmission curve and a limiting flux. Then, the redshift range is converted to a comoving volume.…”
Section: Survey Volumementioning
confidence: 99%
“…Many surveys, targeting emission-line galaxies at z < ∼ 2, have been conducted so far (e.g., Bunker et al 1995;Thompson et al 1996;Moorwood et al 2000;van der Werf et al 2000;Fujita et al 2003;Doherty et al 2006;Shioya et al 2008;Villar et al 2008;Dale et al 2010;Ly et al 2007;Ly et al 2011;Bayliss et al 2011;Lee et al 2012;Best et al 2013;Colbert et al 2013;Ciardullo et al 2013;Drake et al 2013;Pirzkal et al 2013;Sobral et al 2013;Sobral et al 2015;An et al 2014;Khostovan et al 2015;Comparat et al 2015;Comparat et al 2016;Stroe & Sobral 2015;Stroe et al 2017). As a result, the cosmic SFR density has been established with a peak at z = 1-3 and then a gradually decline towards the local Universe (e.g., Hopkins & Beacom 2006;Madau & Dickinson 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cowie et al 2010;Barger et al 2012;Konno et al 2016;Sobral et al 2017). We also plot the Hα LF interpolated from results of Stroe & Sobral (2015) and Sobral et al (2013) to the redshift we trace for CII] in our survey.…”
Section: Methodsmentioning
confidence: 99%
“…However, this effect has not yet been seen at lower redshifts with large surveys designed to capture the bright end well (e.g. Hα LF at z ∼ 0.2 and 0.8, Stroe & Sobral 2015;Sobral et al 2013). This might indicate that at these moderate redshifts, CII] can be significantly triggered in the shocks around more evolved, 'maintenance-mode' galaxies which are accreting at smaller rates (e.g.…”
Section: Cii] Emitters At Z ∼ 068mentioning
confidence: 99%